Datasets for reporting of soft-tissue sarcoma: recommendations from the International Collaboration on Cancer Reporting (ICCR) - Dei Tos, Angelo Paolo; Webster, Fleur; Agaimy, Abbas; Bovée, Judith; Dickson, Brendan; Doyle, Leona; Dry, Sarah; Gronchi, Alessandro; Hameed, Meera; Hemmings, Chris; Liegl-Atzwanger, Bernadette; Thway, Khin; et al. (Histopathology, 2023)
Aims: Soft-tissue tumours are rare and both accurate diagnosis and proper treatment represent a global challenge. Current treatment guidelines also recommend review by specialised pathologists. Here we report on international consensus-based datasets for the pathology reporting of biopsy and resection specimens of soft-tissue sarcomas. The datasets were produced under the auspices of the International Collaboration on Cancer Reporting (ICCR), a global alliance of international pathology and cancer organisations. Methods and results: According to the ICCR's guidelines for dataset development, an international expert panel consisting of pathologists, a surgical oncologist, and a medical oncologist produced a set of core and noncore data items for biopsy and resection specimens based on a critical review and discussion of current evidence. All professionals involved were subspecialised soft-tissue sarcoma experts and affiliated with tertiary referral centres. Commentary was provided for each data item to explain the rationale for selecting it as a core or noncore element, its clinical relevance, and to highlight potential areas of disagreement or lack of evidence, in which case a consensus position was formulated. Following international public consultation, the documents were finalised and ratified, and the datasets, which included a synoptic reporting guide, were published on the ICCR website. Conclusion: These first international datasets for soft-tissue sarcomas are aimed to promote high-quality, standardised pathology reporting. Their adoption will improve consistency of reporting, facilitate multidisciplinary communication, and enhance comparability of data, all of which will help to improve patient's management.
CRIS-Team Scopus Importer:2023-01-27
Keywords: biopsy; checklist; dataset; guidelines; ICCR; resection; soft-tissue sarcoma; synoptic report